Isolated fallopian tube torsion in young females: A case series - Bochra Aziza; Yasmine Houas; Asma Slimani; Riadh Jouini (Journal of Pediatric Surgery Case Reports)
Introduction: Isolated fallopian tube torsion (IFTT) is rare in the pediatric population. Its diagnosis is not always straightforward. Case presentation: Case 1: A 10-year-old premenarchal girl presented after four days of intermittent right iliac fossa pain, nausea, and vomiting. Pelvic ultrasound (US) initially suggested a left ovarian torsion, showing an enlarged, 60 × 50 mm left ovary with no Doppler flow. She was taken to the operating room for an exploratory laparoscopy. We found an IFTT, with a totally normal left ovary. The left fallopian tube was completely necrotic, so a salpingectomy was done preserving the ovary. Case 2: A 13-year-old girl was admitted after 48 hours of pelvic pain and vomiting. US and computerized tomography (CT) scan showed an enlarged left ovary with preserved vascular flow, and an adjacent 32 x 25-mm cystic tubular formation. Suspecting ovarian torsion, she was taken to the operating room for an exploratory laparoscopy. The right fallopian tube was torsed, whereas the right ovary was normal. The left ovary and the left Fallopian tube were normal as well. Despite having a bluish discoloration after the detorsion, the right Fallopian tube was preserved. Case 3: A 12-year-old girl presented to our emergency department with severe intermittent abdominal pain and bilious vomiting. Abdominal US suggested IFTT, so she underwent a laparoscopic exploration. The right fallopian tube was enlarged and torsed. The right ovary was normal. We confirmed good reperfusion after the detorsion, so the right Fallopian tube was preserved. No obvious etiology for the torsion was found. Conclusion: IFTT in young females is rare and can be misdiagnosed as ovarian torsion on US or CT studies.